Pengaruh Pendidikan Kesehatan Dengan Media Booklet Terhadap Peningkatan Pengetahuan Remaja Tentang Infeksi Menular Seksual (IMS) Di SMAS Diponegoro Tumpang Kabupaten Malang - Zhamita, Nafa Eka; Mansur, Herawati; Rosmalawati, Ni Wayan Dwi (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
The phenomenon of promiscuity and public sex among Indonesian teenagers is increasingly worrying. Adolescents have the highest rate of STI infection compared to other age groups. The low level of knowledge among adolescents is one of the reasons why theÂ incidence of sexually transmitted diseases among adolescents is high. Health education through booklets is a way to increase knowledge for adolescents. The purpose of this study was to determine the impact of health education using pamphlets in increasing adolescents' knowledge about sexually transmitted infections (STIs) in SMAS Diponegoro Tumpang, Malang Regency. The design of this study was a pretest design with a single-group pretest-posttest design. The population used was class XI SMAS Diponegoro Tumpang with a total of 89 people and a sample of 40 people using proportional stratified random sampling technique. The instrument used in this study was a questionnaire. Analyze the data using the Wilcoxon signed rank test and the results obtain p-value = 0.000, so we can conclude that the p-value is less than (0.000 <0.05), we it can be concluded that there exists an effect of health education by media booklet to increase adolescents' knowledge about sexually transmitted infections (STIs) at SMAS Diponegoro Tumpang, Malang Regency. In addition to being easy to read anytime, anywhere, textbooks also have another advantage: they have images that can attract and arouse the interest of educational subjects in reading.